STAT5 Regulation of Sex-Dependent Hepatic CpG Methylation at Distal Regulatory Elements Mapping to Sex-Biased Genes - Hao, Pengying (Mol Cell Biol, 2021)
Growth hormone-activated STAT5b is an essential regulator of sex-differential gene expression in mouse liver; however, its impact on hepatic gene expression and epigenetic responses is poorly understood. Here, we found a substantial, albeit incomplete loss of liver sex bias in hepatocyte-specific STAT5a/STAT5b (collectively, STAT5)-deficient mouse liver. In male liver, many male-biased genes were downregulated in direct association with the loss of STAT5 binding; many female-biased genes, which show low STAT5 binding, were derepressed, indicating an indirect mechanism for repression by STAT5. Extensive changes in CpG methylation were seen in STAT5-deficient liver, where sex differences were abolished at 88% of ∼1,500 sex-differentially methylated regions, largely due to increased DNA methylation upon STAT5 loss. STAT5-dependent CpG hypomethylation was rarely found at proximal promoters of STAT5-dependent genes. Rather, STAT5 primarily regulated the methylation of distal enhancers, where STAT5 deficiency induced widespread hypermethylation at genomic regions enriched for accessible chromatin, enhancer histone marks (histone H3 lysine 4 monomethylation [H3K4me1] and histone H3 lysine 27 acetylation [H3K27ac]), STAT5 binding, and DNA motifs for STAT5 and other transcription factors implicated in liver sex differences. Thus, the sex-dependent binding of STAT5 to liver chromatin is closely linked to the sex-dependent demethylation of distal regulatory elements linked to STAT5-dependent genes important for liver sex bias.